Appraisal of Change in Regional and Global Financial Crisis (A Study of Investors’ Behaviour during and after the Speculative Bubbles and Crash of the Nigerian Capital Market) - Nduka , Joseph Afamefuna (African Journal of Education,Science and Technology (AJEST), 2013)
The appraisal of the aggregate market in respect to high price earnings ratio and high asset prices experienced in the equity and asset markets in the end of 1990s and the imminent fall in 2008 ascribed to the speculative bubble crash which is consistent with investors‟ irrational behaviour, wrong human judgement of the 2008 market decline due to bad credit lending. It is against this background that the study appraises how investors are influenced by these biases and what influenced them to change their investment portfolio during and after the speculative bubble and crash of 1998 to 2009. The use of questionnaires was adopted to get an understanding of what investors‟ trading pattern was like; it looked at the behavioural bias that influenced their method of stock picking in the past. The performance of the market after the crash was tested using total market capitalization as a proxy. Among the variables, stocks and equity were positive with 1.021 and 0.055 while interest rate and bonds negat ive at -0.033 and -0.126. Equity was insignificant. This result shows that the fundamental value of a company did not affect market overvaluation. This supports the EMH theory that investors think that they can predict and outperform the market. Conclusively, the common knowledge of the factors underlying the speculative bubble before its imminent burst and the way psychological factors influence decision - making should stand as a guide against a reoccurrence of this phenomenon and improve the efficiency of today‟s reviving financial market.